The conundrum of social class: Disparities in publishing among STEM students in undergraduate research programs at a Hispanic majority institution. Issue 2 (10th December 2017) - Grineski, Sara; Daniels, Heather; Collins, Timothy; Morales, Danielle X.; Frederick, Angela; Garcia, Marilyn
Abstract: Research on the science, technology, engineering, and math (STEM) student development pipeline has largely ignored social class and instead examined inequalities based on gender and race. We investigate the role of social class in undergraduate student research publications. Data come from a sample of 213 undergraduate research participants majoring in STEM at a Hispanic‐majority institution. Based on generalized estimating equations that adjust for student demographics, research confidence, mentoring experiences, duration/number of research experiences, and clustering by major, we find that higher income students and continuing‐generation students (vs. first‐generation students) were significantly more likely to publish. Continuing‐generation students had an even greater likelihood of publishing than first‐generation students as students accrued more research confidence, spent more hours/week with faculty mentors, and conducted research for more months. Results suggest that undergraduate research programs designed to enhance diversity may help close some gaps (e.g., gender) but inadvertently reproduce class inequalities.